Pengaruh Audit Internal dan Efektivitas Pengendalian Internal Terhadap Pencegahan Kecurangan (Fraud) Pada Bank Bumn di Denpasar - Komang Yoga Mahendra; A.A.A Erna Trisna Dewi; Gst Ayu Intan Saputra Rini (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aim to see how the influence of internal audit and internal control on fraud prevention at state-owned banks in Denpasar. The method of data analysis was carried out by means of a questionnaire to all bank employees who were respondents as many as 80 people. The data analysis technique used is multiple linear regression analysis F test, t statistical test, coefficient of determination (R2) and classical assumptions consisting of normality test, multicollinearity test, and hetero cedasticity test. Based on the results of the t statistical hypothesis test, it explains that internal audit has a positive effect on fraud prevention at BUMN Banks in Denpasar, the authorities have a positive effect on fraud prevention at BUMN Banks in Denpasar. Based on the results of the F hypothesis test, it explains that the internal audit variable has a positive and significant effect on the fraud prevention variable at BUMN Banks in Denpasar.